STARCH/PULP-FIBER BASED PACKAGING FOAMS AND CAST FILMS CONTAINING ALASKAN FISH BY-PRODUCTS (WASTE) - Syed H. Imam; Bor-Sen Chiou; Delilah Woods; Justin Shey; Gregory M. Glenn; William J. Orts; Rajnesh Narayan; Robert J. Avena-Bustillos; Tara H. McHugh; Alberto Pantoja; Peter J. Bechtel (BioResources, 2008)
Baked starch/pulp foams were prepared from formulations containing zero to 25 weight percent of processed Alaskan fish by-products that consisted mostly of salmon heads, pollock heads, and pollock frames (bones and associated remains produced in the filleting operation). Fish by-products thermoformed well along with starch and pulp fiber, and the foam product (panels) exhibited useful mechanical properties. Foams with all three fish by-products, ranging between 10 and 15 wt%, showed the highest flexural modulus (500-770 Mpa). Above 20% fiber content, the modulus dropped considerably in all foam samples. Foam panels with pollock frames had the highest flexural modulus, at about 15% fiber content (770 Mpa). Foams with salmon heads registered the lowest modulus, at 25% concentration. Attempts were also made to cast starch-glycerol-poly (vinyl alcohol) films containing 25% fish by-product (salmon heads). These films showed a tensile strength of 15 Mpa and elongation at break of 78.2%. All foams containing fish by-product degraded well in compost at ambient temperature (24oC), loosing roughly between 75-80% of their weight within 7 weeks. The films degraded at a much higher rate initially. When left in water, foams prepared without fish by-product absorbed water much more quickly and deteriorated faster, whereas, water absorption in foams with fish by-product was initially delayed and/or slowed for about 24 h. After this period, water absorption was rapid.